DEPORTATSIYA SIYOSATI VA TALQINI (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract In this article, the coverage of the forced relocation policy of the Soviet state in the sources of Western historiography, as well as the study of the deportation policy by the researchers of the countries, the emergence of the deportation policy of the Soviet state is widely covered.